2011
DOI: 10.4028/www.scientific.net/amr.233-235.2648
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on the Decomposition Laws of Limestone during Converter Steelmaking Process by Static Decomposition Model under Constant Temperature

Abstract: Variations of decomposition rate and decomposition layer thickness of six spherical limestone particles with different sizes are calculated and compared with each other by the experiments and model of static decomposition of limestone under constant temperature. The results indicate that: the decomposition process of limestone can be explained by unreacted core model (UCM) when it is heated sharply; the decomposition rate of large particle is greater than that of small one; the smaller particle size, the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…For easy figures, limestone particle charged into convertor is regarded as a regular sphere. Li Hong's research suggest [3,4] that the process of limestone decomposition is proceeding constantly in convertor, making the new surface of limestone ball surrounded by slag and rising the temperature of new surface suddenly up to the environmental temperature T W . Choosing the outside edge of limestone particle as 0 point of coordinate system, and supposing temperature distribution of limestone particle changing along radial direction, the temperature distribution of globular limestone at different time in convertor is shown in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…For easy figures, limestone particle charged into convertor is regarded as a regular sphere. Li Hong's research suggest [3,4] that the process of limestone decomposition is proceeding constantly in convertor, making the new surface of limestone ball surrounded by slag and rising the temperature of new surface suddenly up to the environmental temperature T W . Choosing the outside edge of limestone particle as 0 point of coordinate system, and supposing temperature distribution of limestone particle changing along radial direction, the temperature distribution of globular limestone at different time in convertor is shown in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the conventional lime steelmaking process, the dissolution of limestone is accompanied by the decomposition reaction of limestone in the limestone steelmaking process. The decomposition of limestone in converter slag is a strong endothermic reaction which has been studied by many researchers [13][14][15]. Deng et al [16] studied the dissolution of limestone in slag at 1600°C and concluded that the structure of the decomposed limestone became very dense at the boundary, resulting in a dense CaO layer at the surface of the generated lime.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional lime steelmaking process, the dissolution of limestone is accompanied by the decomposition reaction of limestone in the limestone steelmaking process. The decomposition of limestone in converter slag is a strong endothermic reaction which has been studied by many researchers [1315]. Deng et al.…”
Section: Introductionmentioning
confidence: 99%